Formulation of a spicy sauce made of pulp of cocona (Solanum sessiliflorum), yellow pepper (Capsicum baccatum) and Charapita chili (Capsicum chinense) - Terry Calderón, Victor Manuel (2018)
It was formulated a spicy coconut sauce with yellow chili and chili peppers, of excellent organoleptic quality and with a longer shelf life; Three spicy sauce formulations were evaluated, which were subjected to a verbal hedonic sensorial analysis (1-5), from which a formulation of greater acceptance was obtained, which was carried out a study of life, microbiological and physicochemical analyzes.The optimum formulation of hot sauce corresponded to Cocona 70%, yellow pepper 20% and pepper 10% charapita, which presented the following proximal composition per 100 grams, humidity 90,4%, proteins 1,0%, ashes 3,3%, fats 1.0%, Carbohydrates 4,3%, and calories 30,2%.The duration of the microbiological tests was five weeks, after which time the molds and yeasts exceeded the allowable limits (103) for consumption; being verified that the useful life is of 12 days, with reference to the Sanitary Norm (NTS N ° 071).